Formal Foundations of Computer Science 1 (Errata)

RISC-Linz logo

Wolfgang Schreiner
  1. A.3/290, last line of Definition 141 (14.10.1999, Werner Danelczyk-Landerl)

    Replace

    forall x0, ..., xn-1, y: f(x0, ..., xn-1) = y <=> (<x0, ..., xn-1> in A /\  y = T).
    by
    forall x0, ..., xn-1: <x0, ..., xn-1> in A => f(x0, ..., xn-1) = T.
  2. 2.2/12, last line of Proposition 1 (15.10.1999, 4.1.2000, Wolfgang Schreiner)

    Drop

    (usually x is free in A).
  3. 2.3.4/39, last line of Proposition 15 (15.10.1999, Wolfgang Schreiner)

    Add

    (usually x is free in A).
  4. 7.1/229, Proposition 114 (15.10.1999, Wolfgang Schreiner)

    Replace

    forall S, R: R is equivalence class on R => x in [x]R.
    by
    forall S, R: R is equivalence relation on S => forall x in S: x in [x]R.
  5. 4.1/101, Proposition 38 (2.11.1999, Wolfgang Schreiner)

    Replace

    for every formula F:
       (F(0) /\  forall x in N: F(x) => F(x+1)) => forall x in N: F(x).

    by

    forall F:
       (F(0) /\  forall x in N: F(x) => F(x+1)) => forall x in N: F(x).
    where the quantified variable F denotes a unary relation.
  6. 4.1/107, Definition 41 (2.11.1999, Wolfgang Schreiner)

    Replace

    A number greater than 1 is  prime (prim) if its only divisors are are 1 and itself:

    by

    A number greater than 1 is  prime (prim) if its only divisors are 1 and itself:
  7. 4.5/124, Definition 51 (2.11.1999, Wolfgang Schreiner)

    Replace

    x * y := ((x0 *R y0) -R (x1 *R y1)) + ((x0 * R y1) + (x1 *R y0))i;

    by

    x * y := ((x0 *R y0) -R (x1 *R y1)) + ((x0 * R y1) +R (x1 *R y0))i;
  8. 4.2/112, Proof of Proposition 44 (2.11.1999, Wolfgang Schreiner)

    Replace

    (x+(-y))+y = (associativity of+)

    by

    (x+(-y))+y = (associativity of +)
  9. 4.7.2/130,133, Definitions 56 and 57 (2.11.1999, Wolfgang Schreiner)

    Replace "for some x" by "for every x".

  10. 3.5/94, Definition 30 (7.11.1999, Clemens Holzmann)

    Replace

    s is a finite sequence over S : <=>
       exists n in N: s is a sequence of length n over S.
    by
    s is a finite sequence over S : <=>
       exists n in N: s is a sequence of length n over S.
  11. 3.5/97, Example (7.11.1999, Clemens Holzmann)

    Replace

    A0 = 0, A1 =0, A2 = 3; A3=1; A4=2.

    by

    A0 = 0, A1 =0, A2 = 3; A3=1; A4=1.
  12. 4.1/104, erster Satz (9.11.1999, Student)

    Replace

    x <= a /\  x < b

    by

    a <= x /\  x < b
  13. 4.7.2/130 (16.11.1999, Bernhard Aichinger)

    Replace

    is used to denote (sum0 <= i <= a T).

    by

    is used to denote (suma <= i <= b T).
  14. 4.7.2/133 (16.11.1999, Wolfgang Schreiner)

    Replace

    (prodx, F T) = T[x <- y] + (prodx, F /\  x != y T)).

    by

    (prodx, F T) = T[x <- y] * (prodx, F /\  x != y T)).
  15. 4.7.3/136 (16.11.1999, Wolfgang Schreiner)

    Replace

    (n k) = (prodn-k+1 <= i <= n i)/(prod1 <= i <= n i).

    by

    (n k) = (prodn-k+1 <= i <= n i)/(prod1 <= i <= k i).
  16. 4.7.5/141, Definition 64 (16.11.1999, Wolfgang Schreiner)

    Replace

    [ ]: Poly x R -> R
    p[a] := (sum0 <= i <= deg(p) pi*ai).

    by

    [ ]: Poly x R -> R
    p[a] := (sum0 <= i <= deg(p) pi *R ai).
  17. 4.7.5/141, Proposition 63 (16.11.1999, Wolfgang Schreiner)

    Replace

    cPoly[a] = cPoly,
    x[a] = aPoly,
    (p+q)[a] = p[a] + q[a],
    (p*q)[a] = p[a] * q[a].

    by

    cPoly[a] = c,
    x[a] = a,
    (p+q)[a] = p[a] +R q[a],
    (p*q)[a] = p[a] *R q[a].
  18. 4.7.5/142, Example (16.11.1999, Wolfgang Schreiner)

    Replace

    (x+1)[2] = 2+1 (= 3Poly)
    (x*x)[2] = 2*2 (= 4Poly)
    (x*x+2*x+1)[3] = 3*3+2*3+1 (= 16Poly)

    by

    (x+1)[2] = 2+1 = 3
    (x*x)[2] = 2*2 = 4
    (x*x+2*x+1)[3] = 3*3+2*3+1 = 16
  19. 3.3/82, after Definition 27 (16.11.1999, Student)

    Replace

    a in A /\  c in C

    by

    a in domain(R) /\  c in range(S)
  20. 6.2/178, Proposition 76 (18.11.1999, Wolfgang Schreiner)

    Replace

    Proposition

    by

    Definition
  21. 5.1/146, Definition 66 (23.11.1999, Martin Reichör)

    Replace

    is the  base formula in which f does not occur and where every application of f in the  recursion formula

    by

    is the  base formula in which p does not occur and where every application of p in the  recursion formula
  22. 6.2/183, Proposition 82 (24.11.1999, Werner Danielczyk-Landerl)

    Replace

    The number of permutations of length n is 2n:
    forall n in N: |{f: f is permutation of length n}| = 2n.

    by

    The number of permutations of length n is n!:
    forall n in N: |{f: f is permutation of length n}| = n!.
  23. 6.2/183, Proof of Proposition 82 (24.11.1999, Werner Danielczyk-Landerl)

    Replace

    Assume |{f: f is permutation of length n}| = 2n.

    by

    Assume |{f: f is permutation of length n}| = n!.
  24. 6.3/188 (24.11.1999, Werner Danielczyk-Landerl)

    Replace

    Thus we can define a "polar" variant of C
    C' := R x [0,2pi[
    assuming that angles are uniquely expressed in "radians" (i.e., pi = 180 o ).

    by

    Thus we can define a "polar" variant of C
    C' := (R> 0 x [0,2pi[) union {<0,3 pi /2>}
    where we assume that angles are uniquely expressed in "radians" (i.e., pi = 180 o ) and assign to the zero point the unique (but arbitrary) angle 3 pi /2 (see the definition of "polar" given below).
  25. 6.2/180, Proposition 80 (24.11.1999, Werner Danielczyk-Landerl))

    Replace

    Every set is smaller than the set of all functions into it:
    forall A, B: B is smaller than A -> B.

    by

    Every set is smaller than the set of all functions from an infinite domain into it:
    forall A, B: A is infinite => B is smaller than A -> B.
  26. 5.2/148 (23.11.1999, Wolfgang Schreiner)

    Replace

    (4) n+1 < 2n+1 <= 2n+2n = 2*2n = 2n+1

    by

    (4) n+1 < 2n+1 <= 2n+2n = 2*2n = 2n+1
  27. 5.4/160 (23.11.1999, Wolfgang Schreiner)

    Replace

    for some constructors "empty" and "tree".

    by

    for some constructors "empty" and "node".
  28. 5.4/161 (23.11.1999, Wolfgang Schreiner)

    Replace

    An element of "Formula" is "forall(X, and(T, or(T, F)))" (assuming X in "Variable").

    by

    An element of "Formula" is "forall(X, and(T, and(T, T)))" (assuming X in "Variable").
  29. 5.4/162 (23.11.1999, Wolfgang Schreiner)

    Replace

    value: Term -> N
    value(0) := 0N
    value(1) := 1N
    value(-x) := -Nvalue(x)
    value(x+y) := value(x)+Nvalue(y)
    value(x*y) := value(x)*Nvalue(y)

    by

    value: Term -> Z
    value(0) := 0Z
    value(1) := 1Z
    value(-x) := -Zvalue(x)
    value(x+y) := value(x)+Zvalue(y)
    value(x*y) := value(x)*Zvalue(y)
  30. B.5.2/324, Proposition 155 (Werner Danielczyk-Landerl, 24.11.1999)

    Replace

    (exists x: A) /\  (exists x: B)
    (exists x: A /\  B)

    by

    (exists x: A /\  B)
    (exists x: A) /\  (exists x: B)
  31. 6.4/198, Example (Clemens Holzmann, 24.11.1999)

    Change the example to

    Let s := [(-1)i*1/i]i. We show that s converges to 0. Take arbitrary epsilon > 0. We have to find some n in N such that
    forall i >= n: |(-1)i*1/i - 0| < epsilon
    which can be simplified to
    forall i >= n: 1/i < epsilon .
    Take n := such n in N: 1/ epsilon < n. Because epsilon > 0, we know 1/ epsilon in R>0. Because N is unbounded (i.e., forall r in R: exists n in N: r < n), we know 1/ epsilon < n and thus n > 0.

    Take arbitrary i >= n. We then know i > 0 and

    1/i <= 1/n < 1/1/ epsilon = epsilon .
  32. 6.1/167, Definition 71 (Wolfgang Schreiner, 24.11.1999)

    Replace

    f is  surjective (surjektiv) (also called  onto) if it

    by

    f is  surjective (surjektiv) (also called  onto) if
  33. 6.4/192, Definition 80 (Wolfgang Schreiner, 26.11.1999)

    Replace

    f is  monotonically decreasing (monoton wachsend)

    by

    f is  monotonically decreasing (monoton fallend)

    Replace

    f is  strictly monotonically decreasing (streng monoton wachsend)

    by

    f is  strictly monotonically decreasing (streng monoton fallend)
  34. 6.4/194, Definition 81 (Wolfgang Schreiner, 26.11.1999)

    Replace

    f has a lower bound (untere Schranke) L, if every element of f is lower than or equal L:
    L is lower bound of f : <=> f: N -> R /\  forall i in N: fi <= L.

    by

    f has a lower bound (untere Schranke) L, if every element of f is greater than or equal L:
    L is lower bound of f : <=> f: N -> R /\  forall i in N: fi >= L.
  35. 6.5/205, Definition 87 (Wolfgang Schreiner, 26.11.1999)

    Replace

    (f+g)(x) := f(x) - g(x);

    by

    (f-g)(x) := f(x) - g(x);
  36. 6.5/207 (Wolfgang Schreiner, 26.11.1999)

    Replace

    if we shift it up one unit, it lies completely above the floor function

    by

    if we shift it up one unit, it lies completely above the ceiling function
  37. B.4/316, first paragraph (Student, 30.11.1999)

    Replace

    If we have to show G0 <=> G1 <=> G2, i.e., (G0 <=> G1) /\  (G1 <=> G0),

    by

    If we have to show G0 <=> G1 <=> G2, i.e., (G0 <=> G1) /\  (G1 <=> G2),
  38. B.4/317, after Proposition 145 (Wolfgang Schreiner, 30.11.1999)

    Replace

    K
    G0 /\  G1
    ~~>
    K union {~G0 \/ ~G1}
    F(alse)
    ~~>
    K union ~G0
    F(alse)
    K union ~G1
    F(alse)

    by

    K
    G0 /\  G1
    ~~>
    K union {~G0 \/ ~G1}
    F(alse)
    ~~>
    K union {~G0}
    F(alse)
    K union {~G1}
    F(alse)
  39. B.4/317, Proposition 146 (Wolfgang Schreiner, 30.11.1999)

    Replace

    K
    G0 \/ G1
    ~~>
    K union ~G0
    G1

    by

    K
    G0 \/ G1
    ~~>
    K union {~G0}
    G1
  40. B.4/318, Proposition 148 (Wolfgang Schreiner, 30.11.1999)

    Replace

    For proving the goal F[x <- G(a0, ..., an-1)] where f is a function explicitly defined as
    G(x0, ..., xn-1) := T,
    it suffices to prove G[x <- T[x0 <- a0, ..., xn-1 <- an-1]] (for some terms T, a0, ..., an-1):
    K union {forall x0, ..., xn-1: G(x0, ..., xn-1) = T}
    G[x <- G(a0, ..., an-1)]
    ~~>
    K union {forall x0, ..., xn-1: G(x0, ..., xn-1) = T}
    G[x <- T[x0 <- a0, ..., xn-1 <- an-1]]

    by

    For proving the goal G[x <- F(a0, ..., an-1)] where F is a function explicitly defined as
    F(x0, ..., xn-1) := T,
    it suffices to prove G[x <- T[x0 <- a0, ..., xn-1 <- an-1]] (for some terms T, a0, ..., an-1):
    K union {forall x0, ..., xn-1: F(x0, ..., xn-1) = T}
    G[x <- F(a0, ..., an-1)]
    ~~>
    K union {forall x0, ..., xn-1: F(x0, ..., xn-1) = T}
    G[x <- T[x0 <- a0, ..., xn-1 <- an-1]]

    After the definition: replace

    We have to prove F[x <- G(a0, ..., an-1)]. By definition of G, it suffices to prove G[x <- T[x0 <- a0, ..., xn-1 <- an-1]].

    by

    We have to prove G[x <- F(a0, ..., an-1)]. By definition of F, it suffices to prove G[x <- T[x0 <- a0, ..., xn-1 <- an-1]].
  41. B.5/321, Proposition 152 (Wolfgang Schreiner, 30.11.1999)

    Replace

    K
    G
    ~~>
    K union F
    G
    (F holds in every domain in which K holds).

    by

    K
    G
    ~~>
    K union {F}
    G
    (F holds in every domain in which K holds).
  42. 6.2/176, Proposition 75 (Wolfgang Schreiner, 7.12.1999)

    Replace

    If A is of size n, then A has 2n subsets:
    forall A, n in N:
       |A| = n => |{S in P(S): T}| = 2n.

    by

    If A is of size n, then A has 2n subsets:
    forall A, n in N:
       |A| = n => |P(A)| = 2n.
  43. 6.2/182, Example (Wolfgang Schreiner, 7.12.1999)

    Replace

    t is sorted with respect to <= : <=>
       forall 0 <= i < length(t): ti <= ti+1.

    by

    t is sorted with respect to <= : <=>
       forall 0 <= i < length(t)-1: ti <= ti+1.
  44. 6.3/186 (Wolfgang Schreiner, 7.12.1999)

    Replace

    (x + y)[a] = x(a) +R y(a)
    (x - y)[a] = x(a) -R y(a)
    (-x)[a] = -Rx(a)
    (x * y)[a] = x(a) *R y(a)

    by

    (x + y)[a] = x[a] +R y[a]
    (x - y)[a] = x[a] -R y[a]
    (-x)[a] = -Rx[a]
    (x * y)[a] = x[a] *R y[a]
  45. 6.3/189 (Wolfgang Schreiner, 7.12.1999)

    Replace

    cartesian: C ->iso(*C, *C') C'
    polar: C' ->iso(*C', *C) C

    by

    polar: C ->iso(*C, *C') C'
    cartesian: C' ->iso(*C', *C) C
  46. 6.3/191, Picture (Wolfgang Schreiner, 7.12.1999)

    Replace the picture by

  47. B.3/312 (Gerhard Nussbaum, 6.12.1999)

    Replace

    Again, since we don't know the truth of G for sure, we generally we have two possibilities:

    by

    Again, since we don't know the truth of G for sure, we generally have two possibilities:
  48. 6.4/195, Example (Wolfgang Schreiner, 14.12.1999)

    Replace

    [i3]i has no upper bound and no lower bound.

    by

    [i3*(-1)i]i has no upper bound and no lower bound.
  49. 6.5/207, Picture (Wolfgang Schreiner, 14.12.1999)

    Replace picture by

  50. 4.2/112, After Proof (Michael Petz, 15.12.1999)

    Replace

    Thus our definition of Z meets one of the two requirements stated at the begin of this section.

    by

    Thus our definition of Z meets one of the two requirements stated at the beginning of this section.

    Also on page 117, after proof: replace

    Our definition of Q meets one of the two requirements stated at the begin of this section.

    by

    Our definition of Q meets one of the two requirements stated at the beginning of this section.

    Also on page 121, after example: replace

    Then we have the following result which implies that the problem stated at the begin of this section can be solved.

    by

    Then we have the following result which implies that the problem stated at the beginning of this section can be solved.

    Also on page 124, after Definition 152: replace

    This imaginary constant is the "missing value" that solves the equation stated at the begin of this section.

    by

    This imaginary constant is the "missing value" that solves the equation stated at the beginning of this section.
  51. 6.2/183, Example (Clemens Holzmann, 19.12.1999)

    Replace

    Then
    p o q = [1,2,0,4,3],
    e.g., (p o q)(2) = q(p(2)) = q(4) = 0. We also have
    p-1 = [2,0,1,4,3]
    e.g., p-1(2) = 1 because p(1)=2, and thus
    p o p-1 = p-1 o p = [0,1,2,3,4].

    by

    Then
    r := p o q = [1,2,0,4,3],
    e.g., r(2) = (p o q)(2) = q(p(2)) = q(4) = 0. We also have
    r-1 = [2,0,1,4,3]
    e.g., r-1(2) = 1 because r(1)=2, and thus
    r o r-1 = r-1 o r = [0,1,2,3,4].
  52. 7.1.1/226, Example (Wolfgang Schreiner, 4.1.2000)

    Replace

    Let r(x, y) : <=> x0+y0 = x1+y1. Then r is an equivalence relation on R x R.

    by

    Let r(x, y) : <=> x0+y1 = x1+y0. Then r is an equivalence relation on R x R.
  53. 5.2/153, Proof (Wolfgang Schreiner, 4.1.2000)

    Replace

    Take k:=ka+kb and f(i):=if i < ka then fa(i) else fb(i).

    by

    Take k:=ka+kb and f(i):=if i < ka then fa(i) else fb(i-ka).
  54. 7.1/245, Proposition 124 (Wolfgang Schreiner, 11.1.2000)

    Replace

    i(0Z') = 0Z,
    i(x+Z'y) = x+Zy,
    i(-Z' x) = -Z x,
    i(x-Z'y) = x-Zy,
    i(x*Z'y) = i(x)*Zi(y),
    x <= Z' y <=> i(x) <= Z i(y).

    by

    i(0Z') = 0Z,
    i(x+Z'y) = i(x)+Zi(y),
    i(-Z' x) = -Z i(x),
    i(x-Z'y) = i(x)-Zi(y),
    i(x*Z'y) = i(x)*Zi(y),
    x <= Z' y <=> i(x) <= Z i(y).
  55. 7.1/245, Proof (Wolfgang Schreiner, 11.1.2000)

    Replace the proof by

    Take arbitrary x in Z' and y in Z'. We prove
    i(x+Z'y) = i(x)+Zi(y).
    We know
    i(x+Z'y) = i(I(x0 +N y0, x1 +N y1)).
    Case x0 +N y0 >= x1 +N y1:
    We have
    i(I(x0 +N y0, x1 +N y1)) =
    i(<(x0 +N y0) - (x1 +N y1)>) =
    [<(x0 +N y0) - (x1 +N y1)>] = (definition  ~ Z)
    [<x0 +N y0, x1 +N y1>] = (congruence properties)
    [x] +Z [y] =
    i(x) +Z i(y).
    Case x0 +N y0 < x1 +N y1:
    Proceeds analogously.
  56. 7.1/248, Proposition 126 (Wolfgang Schreiner, 11.1.2000)

    Replace

    i(0Q') = 0Q,
    i(x+Q'y) = x+Qy,
    i(-Q' x) = -Q x,
    i(x-Q'y) = x-Qy,
    i(x*Q'y) = x*Qy,
    i(x-1) = x-1,
    i(x/Q'y) = x/Qy,
    x <= Q' y <=> i(x) <= Q i(y).

    by

    i(0Q') = 0Q,
    i(x+Q'y) = i(x)+Qi(y),
    i(-Q' x) = -Q i(x),
    i(x-Q'y) = i(x)-Qi(y),
    i(x*Q'y) = i(x)*Qi(y),
    i(x-1) = i(x)-1,
    i(x/Q'y) = i(x)/Qi(y),
    x <= Q' y <=> i(x) <= Q i(y).
  57. 7.1/234, Example (Wolfgang Schreiner, 11.1.2000)

    Replace

    B := {x in N: x is odd /\  x is not prime}.

    by

    C := {x in N: x is odd /\  x is not prime}.
  58. 7.1/230, Example (Wolfgang Schreiner, 12.1.2000)

    Replace

    Let r subset R x R such that r(x, y) <=> x0+x1 = y0+y1.

    by

    Let r subset (R x R) x (R x R) such that r(x, y) <=> x0+x1 = y0+y1.
  59. 7.2/253, Definition 116 (Wolfgang Schreiner, 13.1.2000)

    Replace definition by

    A binary relation on S is a  quasi order (Quasi-Ordnung), if it is irreflexive and transitive:
    R is quasi order on S : <=>
       R subset S x S /\ 
       R is irreflexive on S /\ 
       R is transitive on S.
  60. 7.2/261, Before Picture (Wolfgang Schreiner, 13.1.2000)

    Replace

    Please note that an lower (respectively upper bound) of a set S need not be an element of S:

    by

    Please note that a lower (respectively upper) bound of a set S need not be an element of S:
  61. 7.3/270, Definition 128 (Wolfgang Schreiner, 14.1.2000)

    Replace

    A path from x to y has initial node x and terminal node y : <=>

    by

    A path from x to y has initial node x and terminal node y:
  62. 7.3/272, Example (Wolfgang Schreiner, 14.1.2000)

    Replace

    reflexiveN5(E) = {<0, 0>, <1, 1>, <2, 2>, <3, 3>, <4, 4>}.

    by

    reflexiveN5(E) = E union {<0, 0>, <1, 1>, <2, 2>, <3, 3>, <4, 4>}.
  63. 7.3/273, Proposition 132 (Wolfgang Schreiner, 14.1.2000)

    Replace

    forall S, R: R subset S x S =>
       reflexiveS(R) = R union (S x S).

    by

    forall S, R: R subset S x S =>
       reflexiveS(R) = R union {<x, x>: x in S}.
  64. 7.3/260, Definition 120 (Wolfgang Ziegler, 18.1.2000)

    Replace

    If x is an element of S such that no element of S is smaller than S, then x is called a  minimal element (minimales Element) of S.
    ...
    Correspondingly, if x is an element of S such that no element of S is greater than S, then x is called a  maximal element (maximales Element) of S.

    by

    If x is an element of S such that no element of S is smaller than x, then x is called a  minimal element (minimales Element) of S.
    ...
    Correspondingly, if x is an element of S such that no element of S is greater than x, then x is called a  maximal element (maximales Element) of S.
  65. 7.3/263, Definition 123 (18.1.2000, Student)

    Replace

    A  directed graph (gerichteter Graph) is a pair <V, E> of a set V of  vertices (Knoten) or  nodes and a set of E of  edges (Kanten) or  arcs where E is a binary relation on S:

    by

    A  directed graph (gerichteter Graph) is a pair <V, E> of a set V of  vertices (Knoten) or  nodes and a set of E of  edges (Kanten) or  arcs where E is a binary relation on V:
  66. 7.3/263, after Definition 123 (18.1.2000, Wolfgang Schreiner)

    Replace

    Both nodes are then  adjazent.

    by

    Both nodes are then  adjacent.
  67. 7.2/255, Example (18.1.2000, Wolfgang Schreiner)

    Replace

    w := such u in W_n-1: forall i in N_n-1: u_i = w_i+1

    by

    w := such u: exists n in N: w in W_n /\  u in W_n-1 /\  forall i in N_n-1: u_i = w_i+1

    Replace

    w <= _n u : <=> n = 0 \/ w_0 < u_0 \/ (w_0 = u_0 /\  w <= _n-1 u)

    by

    w <= _n u : <=> n = 0 \/ w_0 < u_0 \/ (w_0 = u_0 /\  w <= _n-1 u)
  68. 7.3/270, Definition 128 (25.1.2000, Wolfgang Schreiner)

    Replace

    length(p) := such n in N: p: Nn+1 -> V.

    by

    length(p) := such n in N: exists V: p: Nn+1 -> V.
  69. 7.3/271, Definition 128 (25.1.2000, Wolfgang Schreiner)

    Replace

    p is elementary : <=>
       forall i in Nn, j in Nn: pi = pj => i = j
          where n = length(p).

    by

    p is elementary : <=>
       forall i in Nn, j in Nn: pi = pj => i = j
          where n = 1+length(p).
  70. 7.1/248, Proposition 126 (25.1.2000, Wolfgang Ziegler)

    Replace

    Let Q' denote the old construction of the integers and Q denote the new one.

    by

    Let Q' denote the old construction of the rationals and Q denote the new one.
  71. 7.3/266, Example (25.1.2000, Wolfgang Schreiner)

    Drop the

      return C;
    
  72. 7.3/274, before Trees (25.1.2000, Wolfgang Schreiner)

    Replace

    (see the example on page 105)

    by

    (see the example on page 265)
  73. 7.3/273, after Proposition 133 (26.1.2000, Wolfgang Schreiner)

    Replace

    In other words, the transitive closure of R is the union of all members of the sequence

    by

    In other words, we can compute the transitive closure of R by the sequence
  74. B/308, end of second paragraph (31.1.2000, Wolfgang Ziegler)

    Replace

    if we are given some knowledge, we must able to check it (i.e., its proof).

    by

    if we are given some knowledge, we must be able to check it (i.e., its proof).
  75. B/309, second paragraph (31.1.2000, Wolfgang Ziegler)

    Replace

    the skeleton provided by the proof rules help us
    the skeleton provided by the proof rules helps us
  76. B.5/321, before Proposition 152 (31.1.2000, Wolfgang Ziegler)

    Replace

    and the proof that the square root of 2 is not rational on page 4.4

    by

    and the proof that the square root of 2 is not rational on page 118
  77. B.5/321, Proposition 152 (31.1.200, Wolfgang Ziegler)

    Replace

    if F holds in every domain in which (some of) the formulas in K holds.

    by

    if F holds in every domain in which (some of) the formulas in K hold.

Maintainer: Wolfgang Schreiner
Last Modification: January 31, 2000

[Up] [RISC-Linz] [University] [Search]